2000
DOI: 10.1142/s0129183100000821
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Hypothesis for the Evolution of Sex

Abstract: An asexual set of primitive bacteria is simulated with a bit-string Penna model with a Fermi function for survival. A recent hypothesis by Jan, Stauffer and Moseley on the evolution of sex from asexual cells as a strategy for trying to escape the effects of deleterious mutations is checked. This strategy is found to provide a successful scenario for the evolution of a stable macroscopic sexual population.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…For large β (or "low temperatures," in the language of statistical mechanics), P (m) behaves like a step function [1]. Individuals with m > µ die, those with m < µ survive, and those with m = µ survive with a probability of 1/2.…”
Section: Models For Conversion To Sexmentioning
confidence: 99%
“…For large β (or "low temperatures," in the language of statistical mechanics), P (m) behaves like a step function [1]. Individuals with m > µ die, those with m < µ survive, and those with m = µ survive with a probability of 1/2.…”
Section: Models For Conversion To Sexmentioning
confidence: 99%
“…On testing an hypothesis on the evolution of sex,Örçal et al 1,2 observed that the steady state distribution of mutations in an asexual bacteria model appeared to be similar to that seen for the steady state distribution of sand in the SOC model of Bak et al 3 The genome of each bacterium is represented by a single bit-string. 4 It was pointed out that only with the inclusion of age structure that the bacteria used here may be considered as the Penna model.…”
Section: Introductionmentioning
confidence: 82%
“…Orçal et al 1 observed that the steady state distribution of mutations of the asexual population driven by Muller's ratchet 6 had a shape similar to the steady state distribution of sand in the sandpile model. In this work, we explore the sandpile model and the bacteria model and show that there are significant differences between the two models that prevent the appearance of avalanches on all scales in the biological model.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because of the lack of an explicit genome, intermediate forms of reproduction as meiotic parthenogenesis and hermaphroditism were not simulated. A more realistic model, involving an explicit genome in the form of bitstrings, was more recently used byÖrçal et al [3] to investigate intermediate reproductive regimes. It makes use of a parameter µ, introduced before by Jan et al [4], defined such that only individuals with µ and more mutations exchange genome.…”
Section: Introductionmentioning
confidence: 99%